SPINT2 is hypermethylated in both IDH1 mutated and wild-type glioblastomas, and exerts tumor suppression via reduction of c-Met activation - Liu, Fei (J Neurooncol, 2019)
PURPOSE: Both IDH1-mutated and wild-type gliomas abundantly display aberrant CpG island hypermethylation. However, the potential role of hypermethylation in promoting gliomas, especially the most aggressive form, glioblastoma (GBM), remains poorly understood. METHODS: We analyzed RRBS-generated methylation profiles for 11 IDH1(WT) gliomas (including 7 GBMs), 24 IDH1(MUT) gliomas (including 6 GBMs), and 5 normal brain samples and employed TCGA GBM methylation profiles as a validation set. Upon classification of differentially methylated CpG islands by IDH1 status, we used integrated analysis of methylation and gene expression to identify SPINT2 as a top cancer related gene. To explore functional consequences of SPINT2 methylation in GBM, we validated SPINT2 methylation status using targeted bisulfite sequencing in a large cohort of GBM samples. We assessed DNA methylation-mediated SPINT2 gene regulation using 5-aza-2’-deoxycytidine treatment, DNMT1 knockdown and luciferase reporter assays. We conducted functional analyses of SPINT2 in GBM cell lines in vitro and in vivo. RESULTS: We identified SPINT2 as a candidate tumor-suppressor gene within a group of CpG islands (designated G(T)-CMG) that are hypermethylated in both IDH1(MUT) and IDH1(WT) gliomas but not in normal brain. We established that SPINT2 downregulation results from promoter hypermethylation, and that restoration of SPINT2 expression reduces c-Met activation and tumorigenic properties of GBM cells. CONCLUSIONS: We defined a previously under-recognized group of coordinately methylated CpG islands common to both IDH1(WT) and IDH1(MUT) gliomas (G(T)-CMG). Within G(T)-CMG, we identified SPINT2 as a top cancer-related candidate and demonstrated that SPINT2 suppressed GBM via down-regulation of c-Met activation.